A Study on the Construction of Environmental Image of Four Chinese Banks: Based on Metadiscourse Analysis - Liu, Xiaoqin; Zhang, Yinyin (Advances in Social Sciences Research Journal, 2024)
With the escalating global concern for environmental issues and China's commitment to achieving carbon peaking and neutrality goals, this study aims to investigate how four leading Chinese banks have constructed environmental images through their CSR reports from 2016 to 2021. Utilizing Hyland's (2005) Metadiscourse model and AntConc 3.5.9 for corpus analysis, we quantitatively and qualitatively examine the strategic use of Metadiscourse in these reports. Our findings reveal a dominance of interactive Metadiscourse, particularly transitions and frame markers, which facilitate coherent and structured environmental disclosures. Interactional Metadiscourse, featuring self-mentions and engagement markers etc., underscores the banks' authority and reader engagement. The banks' CSR reports demonstrate commitments to carbon reduction, green finance and credit, ecological agriculture support, and environmental risk management, and then portray proactive environmental images. This research provides insights into how Metadiscourse constructs sustainability discourse in the financial sector, informing ESG reporting and environmental communication strategies.